Optimizing the Role of School Committees in Monitoring Education Funds to Improve the Quality of Education in Indonesia - Nurdiyana; Sulastri; Suwandi (Academy of Education Journal, 2025)
This research examines the strategic role of school committees in improving the quality of education in Indonesia through a systematic literature review method. The background of the research is based on the gap between the ideal legal basis as stipulated in the National Education System Law and its derivative regulations and the realization of implementation in the field, which results in limitations in monitoring the use of education funds, especially School Operational Assistance (BOS) and Special Allocation Funds (DAK). The lack of training, lack of transparency and low stakeholder involvement are the main factors that open up opportunities for corrupt practices and budget irregularities, which have a negative impact on the quality of education services. The purpose of this study is to identify factors that influence the effectiveness of school committees and formulate strategic recommendations to improve supervisory capacity and accountability in the management of education funds. The method used is a systematic literature review, which is a structured approach in collecting, filtering and synthesizing secondary data from various sources such as scientific journals, policy reports, education regulations, as well as official documents from relevant institutions such as Indonesia Corruption Watch and OECD. The results show that despite a strong legal basis, implementation in the field still faces significant operational and structural obstacles. The gap between theory and practice indicates the need for capacity building through structured training programs and the implementation of digital reporting systems to improve transparency. Thus, this study concludes that optimizing the role of school committees is key to improving the quality of national education and suggests policy reforms that focus on improving oversight and active stakeholder participation